Lifelong physical activity as a result of the process of school education in sport culture - Umiastowska, Danuta (Health Promotion & Physical Activity, 2017)
Physical activity has direct effects on good physical and mental health, develops the skills of resourcefulness and independence in children as well as builds confidence and self-esteem. In modern school tremendous mental efforts as well as a high level of self-control are expected from a child in order to gain certain learning skills. This is expected with the minimum physical activity. This situation leads to frustration, fear, and learning anxiety. It also inhibits the enjoyment of learning, human development, spontaneity and creative thinking. The aim of the study is to show how one can shape long-lasting attitudes to undertake physical activity through out the course of one’s life.